KONSEP TUHAN DALAM SERAT KIDUNGAN KAWEDHAR - Nadya Devysa; Siti Nurlaili (Academic Journal of Islamic Principles and Philosophy, 2020)
The concept of God written in "Serat Kidungan Kawedhar" by Sunan Kalijaga is interesting enough to be studied by devotees of Javanese philosophy. Such as the concept of God written in this Serat, particularly regarding the existence of God as "Sangkan Paran" which makes this Serat needs to be reviewed and examined. There are two main problems in this study; concerning the concept of God as Sangkan Paraning Dumadi in the Serat Kidungan Kawedhar and the teachings of the concept of God in Serat Kidungan Kawedhar for todays people life. With a descriptive method, content analysis and verstehen, this research shows that God described in "Serat Kidungan Kawedhar" is called Hartati which is a form of God's manifestation within humans. While to ease the preaching of the messages, it named God by Sang Hyang Guru and Sang Hyang Hayyu. As the depiction of God "Ngadeg Pangawak Teja" which means standing upright with the light, or God is the light path for human life. This Serat is a hymn used by Sunan Kalijaga in Islamizing Java. Furthermore, it contains religious values regarding the seeking of God as a Creator and paths to be united towards God (manunggal marang Gusti). Moreover, Sunan Kalijaga also said in this Serat that humans must be able to understand themselves and their purposes of life by applying tepa slira and keep caring for God through Dhikr, because it will make people closer to God.